All-trans retinoic acid release from biodegradable polyester microcapsules - Brunner, Cornelia Theresa (2008)
[Excerpt] Tissue engineering strategies frequently include a scaffold, living cells and bioactive substances to promote cell growth and guide cell differentiation. The encapsulation in carriers enables protects the bioactivity of those substances upon implantation, avoids being transported by the body fluids and also allows controlling the release rate. Encapsulation materials are preferably biodegradable polymers. In this work, all-trans retinoic acid (atRA) was used as a model bioactive agent; since it was shown that atRA enhances the expression of osteocalcin, a specific osteogenic marker. [...]